UPAYA PENINGKATAN KESEHATAN IBU HAMIL DENGAN PENYULUHAN PRENATAL MASSAGE DI PMB SRI REJEKI DH JABUNG TANON PLUPUH SRAGEN - Hutari Puji Astuti; Christiani Bumi Pangesti; Nur Rakhmawati (Indonesian Collaboration Journal of Community Services, 2021)
Pregnancy in the third trimester can trigger a variety of unpleasant complaints. Hormonal and physical changes during pregnancy can cause changes in sleep and sleep quality. Prenatal massage or pregnancy massage can be done as a way to relieve discomfort and make pregnant women relax and sleep well. Pregnancy massagers will generally adjust their massage techniques in order to relieve some of the complaints that are often experienced by pregnant women, including the emergence of aches or pains in the head, legs, back, and waist. According to the preliminary study obtained at PMB Sri Rejeki DH Jabung, Tanon Village, Plupuh District, Sragen, there are approximately 20 antenatal visits each month. Some of these pregnant women have never done prenatal massage to deal with complaints during pregnancy. But to overcome complaints during pregnancy, the pregnant woman does pregnancy exercises. So that these pregnant women have never had a prenatal massage. The purpose of this community service is that after receiving counseling about prenatal massage, it is hoped that pregnant women at PMB Sri Rejeki DH Jabung Tanon Plupuh Sragen understand about prenatal massage and are willing to do it by coming to the midwife. The methods used in this activity are lectures, questions and answers and demonstrations about prenatal massage. The target of community service activities regarding prenatal massage are pregnant women, especially in the third trimester at PMB Sri Rejeki DH Jabung Tanon Plupuh Sragen. The expected output from community service activities about prenatal massage for pregnant women at PMB Sri Rejeki DH Jabung Tanon Plupuh Sragen is an increase in knowledge of pregnant women about prenatal massage and pregnant women can do prenatal massage at the nearest midwife